Prevalence, demographic, clinical features and its association of comorbid depressive symptoms in patients with schizophrenia - Sari, Sri Padma (International Journal of Psychosocial Rehabilitation, 2017)
Depressive symptoms have been reported in schizophrenic patients since the initial clinical label of the disease. This study aims to examine the prevalence, demographic, and clinical features of comorbid depressive symptoms in patients with schizophrenia in Indonesia. This study was a descriptive design with a survey approach and correlational design with a cross-sectional approach. Total sample of this study was 305 schizophrenic patients. Data were collected using a characteristic data questionnaire (demographic and clinical features) and Calgary Depression Scale for Schizophrenia (CDSS) questionnaire. Among 305 respondents assessed, 112 respondents (36.7%) experienced depression. Most charactheristic of respondents who had depression were aged 24-42 years old, male, single, and unemployed. Factors significantly associated with depression in schizophrenic patients were occupational status, age at onset suffered mental disorder, length of hospital stay and mental disorder diagnoses. Moreover, demographic factors and clinical features comorbid on depressive symptoms can help in determining depression.